Fairy tail. 2 - Mashima, Hiro, 1977-; Flanagan, William (New York : Kodansha Comics, 2008)
Lucy joins forces with the fire wizard Natsu and his flying cat Happy to steal a book from Duke Everlue, but their mission proves to be more dangerous than any of them anticipated.
Translated from the Japanese.
"First published in Japan in 2007 by Kodansha Ltd., Tokyo"--T.p. verso.
"A Kodansha Comics trade paperback original"--T.p. verso.
Book reads from right to left in the traditional Japanese format.
Young Adult
Young Adult
Keywords: Wizards -- Comic books, strips, etc. -- Fiction; Magic -- Comic books, strips, etc. -- Fiction; Good and evil -- Comic books, strips, etc. -- Fiction; Wizards -- Comic books, strips, etc. -- Fiction; Magic -- Comic books, strips, etc. -- Fiction; Good and evil -- Comic books, strips, etc. -- Fiction; Fantasy graphic novels; Manga; Comic books, strips, etc; Graphic novels; Fantasy comic books, strips, etc; Graphic novels